Analysis and insight of electroluminescence imaging in the assessment of potential-induced degradation in crystalline silicon photovoltaic module. (April 2022) - Puranik, Vishal E.; Gupta, Rajesh
Highlights: Unveils the critical aspects of electroluminescence (EL), and potential-induced degradation (PID) involve in PID detection, qualitative and quantitative assessment. Conventional pattern-based PID detection method is useful for simple monitoring of PID only. From a field perspective, the visual pattern-based PID detection method is sluggish in early PID detection and unreliable in some situations. Ohmic component of PID causes significant performance loss of a PV cell than non-ohmic. EL imaging can estimate maximum PID power loss in the range of 25–75% Abstract: Potential-induced degradation (PID) causes a significant drop in the efficiency of a photovoltaic (PV) module, which results in module failure before the expected lifetime. Electroluminescence (EL) imaging has been a commonly used technique in laboratory and field studies for the early diagnosis of PID. This article presents the analysis and insight of EL imaging in qualitative and quantitative assessment of PID. Circuit analysis is presented to discuss the method of visually inspecting defects and the role of EL current in diagnosing PID. The performance of the conventional pattern-based PID detection method suggested in IEC standards is experimentally evaluated. Results show that low current EL imaging acquires characteristic PID pattern early hence useful in the simple monitoring of PID progression. Pattern-based detection becomes unreliable when PID progresses uniformly, or a module contains other shunting defects, which shows a similar appearance to PID in the EL images. Also, visually inspecting PID from the EL images is the sluggish approach when the aim is to detect PID early before it results in significant power loss. The potential of EL imaging in quantifying the impact of PID on module performance is also discussed. It reveals that the use of a high EL current can give maximum PID power loss estimation in the range of 25–75%. This work gives new insights that would help to develop EL methods for effectively diagnosing PID in early stages and preventing module failure.